(untitled) (Al Fiddhoh: Journal of Banking, Insurance, and Finance, 2022)
This study aims to assess and analyze the financial performance of the women’s savings and loan management unit (SPK) Siulak District, Kerinci Regency. Financial performance assessment is seen from two aspects, namely aspects of financial management and aspects of loan management. This study uses secondary data from the financial statements of UPK SPP Siulak District, Kerinci Regency, in the form of UPK income statement and other related reports from 2016 to 2020. Data were analyzed using a financial ratio analysis approach. The results showed that the financial performance of UPK SPP Siulak Subdistrict Kerinci Regency viewed from the aspects of financial management from 2016 to 2020 ranged from intervals of 17.77% -21.15%, including the category of underperformance, while the financial performance of UPK SPP Subdistrict of Siulak District of Kerinci Regency viewed aspects of loan management from 2016 to 2020 ranged from intervals of 1.92% -2.52% including underperforming categories. The results of UPK SPP health assessment in Siulak District Kerinci Regency from 2016 to 2020 were 61.66, including the quite healthy category.